Microwave heating and deicing efficiency for asphalt concrete with SiC–Fe3O4 microwave enhanced functional layer. (15th January 2022) - Liu, Xiaoming; Zhao, Yu; Liu, Weizheng; Yan, Daxiong
Abstract: Traditional deicing methods such as manual deicing, infrared heating deicing, chemical deicing might bring serious environmental pollution and energy consumption. Microwave heating deicing technology with high microwave energy utilization efficiency and environmental protection has been widely studied. But the microwave heating deicing efficiency still cannot meet the practical application requirement at present. In order to improve the microwave deicing efficiency, the asphalt concrete with microwave enhanced functional layer (MEFL) and control specimens (asphalt concrete without MEFL) were designed. In the meanwhile, the effect of SiC–Fe3 O4 content and thickness of MEFL on microwave heating efficiency (MHE) and ice-thawing time were studied. Moreover, the influence of initial temperature and ice layer thickness on ice-thawing time were also evaluated. Finally, the energy utilization efficiency of MEFL was calculated. Results show that the SiC–Fe3 O4 content in MEFL had a positive effect on MHE and ice-thawing time. The MHE and ice-thawing time of 28.6% SiC–Fe3 O4 were 2.42 times and 6.2 times shorter than that of control specimens, respectively. But the MEFL thickness had a negative effect on MHE and ice-thawing time. The ice-thawing time of MEFL with −15 °C initial temperature was 46s. it was increased about 1.7 times in contrast to −5 °C. In addition, the thicker ice layer thickness might increase the ice-thawing time. The ice-thawing time of 30 mm ice layer was 13s longer than that of the 10 mm ice layer. The microwave energy utilization efficiency of 10 mm MEFL could reach 79.21%. Overall, the MEFL can significantly improve the MHE and deicing efficiency of asphalt concrete.